Entrepreneurship in The Light of The Qur’an, Ḥadīth, And Iqbal’s Philosophy - HAYAT, TAHREEM; SHAHEEN, DR. SYEDA SABA; GILLANI, DR. SYED AFRAZ HASSAN; MASOOD, HAFIZA UMAMA (International Journal of Islamic Economics and Governance, 2023)
This research examines the differences between Islamic and Western perspectives on entrepreneurship and linked it with Iqbal’s philosophy so that Muslim entrepreneurs can understand the significance of Islam's guiding principles and teachings as they forge ahead in their ventures. This research highlights all the values, principles, and teachings of Islam concerning entrepreneurship because, in today's dynamical changing world, every Muslim entrepreneur wants to be successful but doesn't value the founding principles. This research is divided into two sections: the first section explains the significance of business activity by citing verses from the Glorious Qur’an and Ḥadīth from the Holy Prophet (PBUH), while the second section uses the poetry of Allama Muhammad Iqbal to emphasize the characteristics and approach of successful business owners and the benefits of adhering to Islamic principles in the course of doing business. Iqbal employed unique words like ‘Khudi’ that are hard to describe and grasp. Khudi was explained differently by each scholar. This study used the concept of khudi as Perceived Entrepreneurial Self‐Efficacy and justify by western scholars of entrepreneurship.